Mucosal immunoglobulins at respiratory surfaces mark an ancient association that predates the emergence of tetrapods - Zhen Xu (Nature Portfolio, 2016)
In teleost fish the gills perform—in addition to respiration—functions such as immune defence. Here the authors show that IgT, a teleost specific Ig previously shown to be involved in gut and skin mucosal immunity, is locally induced in the gill, where it plays a key role in immunity in rainbow trout.